2016
DOI: 10.15376/biores.11.2.3165-3177
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Purification, and Characterization of a Thermostable β-Glucosidase from Thermotoga thermarum DSM 5069

Abstract: A 56-kDa β-glucosidase (TthBgl) derived from Thermotoga thermarum DSM 5069 was expressed and purified from Escherichia coli BL21 (DE3). The purified enzyme showed hydrolytic activity towards only pnitrophenyl-β-D-glucopyranoside among the synthetic glycosides tested. The pH maximum was 5.0, and under the conditions tested, maximal activity was at 85 ºC, and pH stability occurred from 5.0 to 6.0. After being incubated at 80 ºC for 120 min, TthBgl retained 80% of its original activity. The β-glucosidase had no a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…These findings were also reported by Qin et al 11 . The highest β -glucosidase activity was in the presence of FeSO 4, and the lowest activity was in the presence of ZnSO 4, CoCl 2, KH 2 PO 4 NaCl, similar results were also reported in other studies also where β -glucosidase activity declined in the presence of MnSO 4, ZnSO 4 and CoCl 2 11 , 18 .…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…These findings were also reported by Qin et al 11 . The highest β -glucosidase activity was in the presence of FeSO 4, and the lowest activity was in the presence of ZnSO 4, CoCl 2, KH 2 PO 4 NaCl, similar results were also reported in other studies also where β -glucosidase activity declined in the presence of MnSO 4, ZnSO 4 and CoCl 2 11 , 18 .…”
Section: Resultssupporting
confidence: 90%
“…The effects of eight metal ions (Ca 2+ , Co 2+ , Fe 2+ , Mg 2+ , Mn 2+ , Zn 2+ , K + , and Na + ) on β -glucosidase activity were determined at a final concentration of 4 mM at the optimal pH and temperature (4.0 and 65 °C) (Table 8 ). β -Glucosidases were either inhibited or activated by the metal ions 18 . All eight metal ions reduced β -glucosidase activity in Bgl3 by 50% or more in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many β-glucosidases and β-xylosidases have been cloned and characterized from plant, yeast and bacteria, only a few studies about highly thermotolerant and sugar-tolerant β-glucosidases and β-xylosidases have been reported. Thermophilic bacteria, such as Thermotoga thermarum, Thermotoga petrophila and Thermoanaerobacterium saccharolyticum, are well known to produce plentiful glycoside hydrolases with competitive advantages, such as great catalytic ability and excellent pH and temperature stability [39][40][41]. In the previous study, we identified βglucosidase of GH3, Dth3, and β-xylosidase with GH39, Xln-DT, from Dictyoglomus thermophilum, a kind of thermophilic bacteria.…”
Section: Discussionmentioning
confidence: 98%